Goethe: Musical poet, musical catalyst : Proceedings of the conference hosted by the Department of Music, National University of Ireland, Maynooth, 26 & 27 March 2004 - Byrne Bodley, Lorraine (Ireland Caryfort Press, 2004)
The high degree of admiration for Goethe by people of all kinds, including some who were themselves possessed of creative ability of the highest order, and in fields quite different from literature is something unique in the history of European culture. Reasons for the poet's reputation are found not only in his art but in his influence on contemporaries, and on the generation of artists and musicians who came after him Perhaps more than any other writer, Goethe has had a great influence on the European musical heritage which continues down to the present day. Given not just the magnitude of Goethe's genus but its exceptionally forward-looking character. It is little wonder that the attitudes of many gifted artists towards him were ambivalent or antagonistic. The aim of this volume is to address the salent misconception that Goethe was unmusical, and to explore some of the musical riches his poetry has inspired and continues to call forth.